2015
DOI: 10.1038/srep12748
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Bovine Neonatal Pancytopenia-associated vaccine-induced alloantibodies correlates with Major Histocompatibility Complex class I expression

Abstract: Bovine Neonatal Pancytopenia (BNP), a fatal bleeding syndrome of neonatal calves, is caused by maternal alloantibodies absorbed from colostrum and is characterized by lymphocytopenia, thrombocytopenia and bone marrow hypoplasia. An inactivated viral vaccine is the likely source of alloantigens inducing BNP-associated alloantibodies in the dam. In this study the specificity of BNP alloantibodies was assessed and was linked to the pathology of BNP. We demonstrated that Major Histocompatibility Complex class I (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…To manufacture this vaccine, BVD virus is cultured in Madin-Darby bovine kidney (MDBK) cells [30] and, following purification, combined with a novel proprietary adjuvant (Procison-A TM ; a micro-fluidized oil-in-water adjuvant composed of Quil-A, Cholesterol, mineral oil [31]). High levels of residual bovine proteins have been detected in Pregsure© [8,9,32] and alloantibodies from BNP cows have been shown to recognize MDBK cells [8,9,12,19]. Furthermore, experimental immunization of calves with Pregsure© confirmed that vaccination induces alloantibodies that bind MDBK cells and leukocytes [10,19].…”
Section: Vaccination Induces Bnp-associated Alloantibodiesmentioning
confidence: 76%
See 4 more Smart Citations
“…To manufacture this vaccine, BVD virus is cultured in Madin-Darby bovine kidney (MDBK) cells [30] and, following purification, combined with a novel proprietary adjuvant (Procison-A TM ; a micro-fluidized oil-in-water adjuvant composed of Quil-A, Cholesterol, mineral oil [31]). High levels of residual bovine proteins have been detected in Pregsure© [8,9,32] and alloantibodies from BNP cows have been shown to recognize MDBK cells [8,9,12,19]. Furthermore, experimental immunization of calves with Pregsure© confirmed that vaccination induces alloantibodies that bind MDBK cells and leukocytes [10,19].…”
Section: Vaccination Induces Bnp-associated Alloantibodiesmentioning
confidence: 76%
“…Alloantibodies targeting alternative antigens (e.g. VLA-3) were also identified [12], however only anti-MHC I alloantibodies were consistently found in BNP cows and showed correlation with BNP pathology. Thus, overall evidence indicates that BNP alloantibodies are induced by bovine cellular material, specifically MHC I molecules, found in Pregsure© and that these alloantibodies account for the damage to the hematopoietic system seen in BNP.…”
Section: Major Histocompatibility Complex Class I Molecules Are the Mmentioning
confidence: 99%
See 3 more Smart Citations